Epistemic Mapping of Prophethood and Philosophy in the Thought of Al-Farabi: Reconstructing the Relationship between Revelation and Reason in Islamic Intellectual Tradition - Mehmet Burak GÜNEŞ (VIRTUOUS JOURNAL, 2025)
This study aims to analyze the relationship between prophethood (nubuwwah) and philosophy in the intellectual system of Al-Farabi through an epistemic mapping approach. This research employs a qualitative method based on library research, drawing primarily from Al-Farabi’s major works alongside relevant secondary sources. The findings reveal that Al-Farabi does not perceive revelation and reason as contradictory; rather, he situates them within a unified hierarchical epistemological framework. Prophethood represents the highest form of knowledge attained through intellectual emanation, while philosophy constitutes a rational path toward the same truth. Therefore, the relationship between the prophet and the philosopher is complementary rather than dichotomous. This study contributes to a deeper understanding of the integration of knowledge in Islamic intellectual tradition and its relevance for contemporary Islamic epistemology.